COmmuNity-engaged SimULation Training for Blood Pressure Control (CONSULT-BP): A study protocol. Issue 5 (5th February 2021) - Tjia, Jennifer; Pugnaire, Michele; Calista, Joanne; Esparza, Nancy; Valdman, Olga; Garcia, Maria; Yazdani, Majid; Hale, Janet; Terrien, Jill; Eisdorfer, Ethan; Zolezzi-Wyndham, Valerie; Chiriboga, Germán; et al.
Abstract: Background: Healthcare professionals have negative implicit biases toward minority and poor patients. Few communication skills interventions target implicit bias as a factor contributing to disparities in health outcomes. We report the protocol from the COmmuNity-engaged SimULation Training for Blood Pressure Control (CONSULT-BP), a trial evaluating a novel educational and training intervention targeting graduate medical and nursing trainees that is designed to mitigate the effects of implicit bias in clinical encounters. The CONSULT-BP intervention combines knowledge acquisition, bias awareness, and practice of bias mitigating skills in simulation-based communication encounters with racially/ethnically diverse standardized patients. The trial evaluates the effect of this 3-part program on patient BP outcomes, self-reported patient medication adherence, patient-reported quality of provider communication, and trainee bias awareness. Methods: We are conducting a cluster randomized trial of the intervention among cohorts of internal medicine (IM), family medicine (FM), and nurse practitioner (NP) trainees at a single academic medical center. We are enrolling entire specialty cohorts of IM, FM, and NP trainees over a 3-year period, with each academic year constituting an intervention cycle. There are 3 cycles of implementation corresponding to 3 sequential academic years. Within each academic year, we randomize training times to 1 of 5 start dates using a stepped wedge design. The stepped wedge design compares outcomes within training clusters before and after the intervention, as well as across exposed and unexposed clusters. Primary outcome of blood pressure control is measured at the patient-level for patients clustered within trainees. Eligible patients for outcomes analysis are: English-speaking; non-White racial/ethnic minority; Medicaid recipient (regardless of race/ethnicity); hypertension; not have pregnancy, dementia, schizophrenia, bipolar illness, or other serious comorbidities that would interfere with hypertension self-control; not enrolled in hospice. Secondary outcomes include trainee bias awareness. A unique feature of this trial is the engagement of academic and community stakeholders to design, pilot test and implement a training program addressing healthcare. Discussion: Equipping clinicians with skills to mitigate implicit bias in clinical encounters is crucial to addressing persistent disparities in healthcare outcomes. Our novel, integrated approach may improve patient outcomes. Trial registration: NCT03375918 Protocol version: 1.0 (November 10, 2020)